Swedish-Finnish School Word List - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Sweden Finnish school word list contains central terminology for preschool, elementary school and high school, also words from higher education central to high school students planning for graduate studies. Contains 1836 entries. 2014.

Språkrådets svensk-finska skolordlista innehåller central terminologi inom förskola, grundskola och gymnasieskola, även ord från högre utbildning som är centrala för gymnasieelever som planerar eftergymnasiala studier. Svensk-sverigefinsk skolordlista. 1836 uppslagsord. 2014.
Svensk-finsk skolordlista
Keywords: secondary schools; sekundärskolor; schools; skolor; pre-primary schools; förskolor; College Admission Test; Inträdesprov, högskola; glossary; ordlista; school; skola; secondary education; gymnasium; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur